Primary colors - Furnas, Brent (Harlow (Essex, England) : Pearson Education Limited, 1999)
Jack Stanton is a young governor but has more ambitious ideas: he wants to be President of the USA. Henry Burton can help him achieve his dream but he knows Stanton will do almost anything to win. Henry is about to discover the dark secrets in Stanton's past and will then have to decide for himself what is right and wrong. This is not a true story but it is based on recent American Presidents. Because of this, the author has kept his name a secret.
ESO34
Keywords: Lengua inglesa -- Textos